The Outcomes of Modified PAS Model in Smoking Cessation Service by Community Pharmacist - ทองวัตร ศิวรินทร์; สุริยะไกร สมชาย; สุกใส หนึ่งฤทัย (Disease Control Journal, 2018)
The aim of the study was to determine the outcomes of Modified PAS model: a smoking cessation service by community pharmacist. This model is composed of four steps, i.e. 1) active promotion of smoking cessation service in community pharmacy to communities close to community pharmacy 2) discussion the service with smokers willing to quit smoking 3) intensive tobacco-dependence intervention and 4) follow- up session. A quasi-experimental study was conducted. The setting was Mitraparp medical center community, consisting of 15 subcommunities, in Mueang Khon Kaen district. The Modified PAS model was assigned to intervention communities by simple random sampling. The intervention process was active promotion of smoking cessation service by community pharmacy during first 2 weeks, discussion the service with smokers willing to quit smoking, intensive tobacco-dependence intervention and follow-up weekly for 4 weeks, then every month for 3 months. The control group, smokers in control communities, were followed-up with the same schedule by phone calls. The abstinence rates were compared between two groups. In intervention group, 22 smokers were willing to quit smoking during the 2-week active promotion period. The 46 smokers from nearby communities were in control group. The continuous abstinence, prolonged abstinence and 28-day point prevalence abstinence rate in intervention and control group were 18.2% and 2.2 % (p = 0.04), 40.9 % and 8.7% (p = 0.003), 50.0 % and 17.4 % (p = 0.005) respectively. The intervention group expressed strongly satisfaction with smoking cessation service by community pharmacist. In conclusion, this study reveals that abstinence rates in intervention group are significantly greater than control group. In addition, community pharmacists should provide the Modified PAS model to assist smokers willing to quit smoking.